What contributes to family carers' decision to transition towards palliative-oriented care for their relatives in nursing homes? Qualitative findings from bereaved family carers' experiences. Issue 2 (April 2021) - Gonella, Silvia; Clari, Marco; Basso, Ines; Di Giulio, Paola
Abstract: Objectives: Family carers (FCs) of nursing home (NH) residents are best placed to notice deteriorations that signal impending death in their relative, which can open a conversation with healthcare professionals (HCPs) about adjusting the care plan. We explored contributors to bereaved FCs' decision to transition towards palliative-oriented care for their relatives in NHs. Methods: This qualitative descriptive study used a phenomenological design. Thirty-two bereaved FCs across 13 Italian NHs completed semi-structured interviews. Additional data were collected on NH referrals to palliative care services (PCS) in the 6 months before study start and treatments provided in the last week of life. Content analysis with a combined inductive and deductive approach was applied to identify codes and fit them into an a priori framework. When codes did not fit, they were grouped into new categories, which were finally gathered into themes. Results: FCs reported four types of "trigger events" that made them doubt that their relative would recover: (1) physical deterioration (e.g., stopping eating/walking or swallowing problems); (2) social confirmation (e.g., confirming their relative's condition with friends); (3) multiple hospitalizations; and (4) external indicators (e.g., medical examinations by external consultants). A "resident-centered environment" helped FCs recognize trigger events and "raise awareness of the possibility of death"; however, the "need for reassurance" was pivotal to a "gradual transition towards palliative-oriented care". When participants did not recognize the trigger event, their relative continued to receive curative-oriented care. NHs that referred residents to PCS discussed palliative-oriented care more frequently with FCs, had a lower nurse-to-resident and nurse aide-to-resident ratio, and administered more palliative-oriented care. Significance of results: Trigger events represent an opportunity to discuss residents' prognosis and are the starting point for a gradual transition towards palliative-oriented care. Adequate staffing, teamwork, and communication between FCs and healthcare professionals contribute to a sensitive, timely shift in care goals.